Risk factors for left ventricular thrombus formation on transthoracic echocardiography in a propensity-matched case control study. (14th October 2021) - Tang, G H; Wang, A; Markson, L J; Manning, W J; Strom, J B
Abstract: Introduction: The specific risk factors for left ventricular thrombus (LVT) formation on transthoracic echocardiography (TTE) independent of age, sex, and left ventricular ejection fraction (LVEF) remain uncertain. Purpose: To conduct a propensity-matched case control study of LVT. Methods: We queried structured TTE report data from 113, 673 patients at our institution to identify individuals with LVT on TTE, 2000–2011. Cases were matched 1:1 with controls on age, sex, LVEF, inpatient/outpatient status, image quality, test year, blood pressure, heart rate, height, and weight. using propensity scores. Risk factors for LVT formation were determined using medical chart review. Results: Over 12 years, we identified 132 patients with LVT and 132 matched controls (mean age 62.0±16.1 years, 73.1% male, mean LVEF 27.0% ± 16.0%). Cases were similar to controls across all matched variables except height (cases vs. controls, mean height 172.2±8.8 vs. 174.8±9.3 cm, p=0.03). Compared with controls, TTEs for cases were more frequently performed for the indications of myocardial infarction (MI; 28.0% vs. 9.9%, p<0.001) and source of embolism (3.8% vs. 0.0%, p=0.008). Despite no differences between cases and controls in rates of hypertension, hyperlipidemia, diabetes, and thrombophilia (Table), a history of peripheral arterial disease was associated with a 3.4-fold increased odds of LVT formation (univariate odds ratio [OR], 3.35, 1.50–7.47, p=0.003). This association persisted despite adjustment for history of MI, stroke, height, history of recent major bleeding, and receipt of percutaneous coronary intervention (PCI) (adjusted OR, 4.33, 1.66–11.29, p=0.003). On presentation, 22.0% of cases were on anticoagulation including 20.5% on warfarin, none on a direct oral anticoagulant (DOAC), and 1.5% on heparin products. Additionally, 48.5% of cases were on antiplatelet medications. Of the 27 patients on warfarin on diagnosis of LVT, 25.9% had an International Normalized Range (INR) value <2.0. All TTE parameters were similar across groups (p>0.05 for all). Of those with LVT, 54 (40.9%) had LVT resolution over a median of 4.4 (0.9 to 13.6) months. Conclusions: In this single center, propensity-matched case-control study of individuals with LVT on TTE, a history of peripheral arterial disease was associated with a 4.3-fold increased odds of LVT formation independent of age, sex, LVEF, history of MI, stroke, or PCI. Of those with LVT, anticoagulation was used on presentation in 22.0%. Nearly half had LVT resolution within 4.4 months. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The project was funded by a grant from the National, Heart, Lung, and Blood Institute (1K23HL144907 - Strom).